EKSISTENSI KERAJINAN GERABAH TRADISIONAL DI DUSUN PRECET BLITAR MELALUI DESA WISATA EDUKASI KAMPUNG GERABAH - Aprilya Dwi Nurjanah; Aliza Nur Sabila; Novela Wahyu Ramadhani; Joan Hesti Gitapurwasih (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
In contrast to other craftsmen who experienced a decline, the traditional pottery industry in Precet actually experienced an increase. The purpose of the study was to determine the strategy of the pottery craftsmen in Precet Hamlet in maintaining their culture so that traditional pottery crafts still exist. The research was conducted in Precet, Plumpungrejo, Kademangan, Blitar. Using this type of qualitative research with a case study approach. Determination of research subjects by purposive sampling method. Data collection techniques are interviews with five informants, observation, and documentation. as for the data validity technique using source triangulation and data analysis is carried out through the stages of Miles and Huberman. The results of this study are people who still maintain their culture from generation to generation, innovations that continue to be carried out according to market needs, and a supportive surrounding environment so that the traditional pottery industry survives. This research is examined using the theory of structural functionalism from Talcot Parson. Parson coined the famous scheme of functions known as the acronym AGIL. The existence of this research is expected to be used as a motivation to continue to innovate with modern technology that helps facilitate craftsmen in making pottery.